2010
DOI: 10.1016/j.rmed.2010.02.020
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of cognitive behavioral therapy for anxiety and depression in COPD

Abstract: The findings indicate that CBT may provide rapid symptom relief for COPD patients with clinically significant anxiety and depression, and underline the need for integrating mental health care into the overall medical regimen for COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(101 citation statements)
references
References 36 publications
4
95
2
Order By: Relevance
“…In studies with physically healthy people, decreases in catastrophic interpretations and anxiety sensitivity have mediated the effectiveness of cognitive behavior therapy for panic disorder, and cognitive behavior therapy for high anxiety sensitivity has prevented the development of panic-spectrum psychopathology [11,[53][54][55]. In patients with COPD, effective cognitive behavior therapy for panic attacks, and for the prevention of panic-spectrum psychopathology, has been associated with decreased catastrophic interpretations over an 18 month follow-up period [7].…”
Section: Discussionmentioning
confidence: 99%
“…In studies with physically healthy people, decreases in catastrophic interpretations and anxiety sensitivity have mediated the effectiveness of cognitive behavior therapy for panic disorder, and cognitive behavior therapy for high anxiety sensitivity has prevented the development of panic-spectrum psychopathology [11,[53][54][55]. In patients with COPD, effective cognitive behavior therapy for panic attacks, and for the prevention of panic-spectrum psychopathology, has been associated with decreased catastrophic interpretations over an 18 month follow-up period [7].…”
Section: Discussionmentioning
confidence: 99%
“…Whether these improvements are larger than those in the control condition is important. To date, only one study found CBT to have stronger antidepressant effects in COPD patients than standard care [62]. Other studies including one with a waiting list as the control group failed to find significant effects.…”
Section: Effects Of Psychotherapymentioning
confidence: 99%
“…[1][2][3][4] Psychologically based interventions (e.g. cognitive behaviour therapy) have also been used in this same population to manage anxiety, depression, QOL, [5][6][7][8][9][10][11] dyspnoea 12 and exercise tolerance. 13 Over the last decade, four systematic reviews (with and without meta-analysis) have examined the evidence base for psychologically based interventions to alleviate anxiety and depression in people with COPD [14][15][16][17] with one systematic review for adults with asthma.…”
Section: Introductionmentioning
confidence: 99%